2017
DOI: 10.18865/ed.27.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Detemir in Combination with Oral Antidiabetic Drugs Improves Glycemic Control in Persons with Type 2 Diabetes in Near East Countries: Results from the Lebanese Subgroup

Abstract: Objective: To evaluate the effectiveness and safety of insulin detemir treatment as add-on therapy in a real-world setting of Lebanese insulin naïve persons, with type 2 diabetes poorly controlled on oral antidiabetic drugs (OADs). Methods:Our study was a prospective, observational study representing the Lebanese arm of the multinational prospective and observational study involving 2,155 persons across Near East countries, Lebanon, Pakistan, Israel and Jordan. Effectiveness endpoints were changes in HbA1c, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…A study conducted by Seufert J et al [ 25 ] demonstrated that switching the basal insulin to Gla-300 in basal insulin supported oral regimen improved metabolic control and treatment satisfaction with a decreased risk of symptomatic and nocturnal hypoglycemia and without weight gain. It is evident that insulin detemir implemented as an add-on therapy to OADs improved glycemic control without increased risk of hypoglycemia, adverse events or body weight compared with baseline [ 26 ].…”
Section: Currently Used Basal Insulin Analoguesmentioning
confidence: 99%
“…A study conducted by Seufert J et al [ 25 ] demonstrated that switching the basal insulin to Gla-300 in basal insulin supported oral regimen improved metabolic control and treatment satisfaction with a decreased risk of symptomatic and nocturnal hypoglycemia and without weight gain. It is evident that insulin detemir implemented as an add-on therapy to OADs improved glycemic control without increased risk of hypoglycemia, adverse events or body weight compared with baseline [ 26 ].…”
Section: Currently Used Basal Insulin Analoguesmentioning
confidence: 99%
“…Penurunan KGDP pada kelompok yang mendapat terapi kombinasi OAD + insulin terlihat paling besar diantara terapi lannya. Hal ini didukung oleh hasil penelitian Echtay et al, (2017) yang menunjukan ratarata KGDP pasien mengalami penurunan yang signifikan dari 213,7±60,1 mg/dL menjadi 120,3±25,7 mg/dL (p<0,0001). Penggunaan insulin yang dikombinasikan dengan OAD pada pasien DM tipe 2 dikatakan dapat meningkatkan kontrol glikemik pasien tanpa adanya peningkatan kejadian hipoglikemi dan peningkatan berat badan pada pasien.…”
Section: Perubahan Rata-rata Kgdpunclassified